Comparison of perioperative, oncologic, and functional outcomes between 3D and 2D laparoscopic radical prostatectomy: a systemic review and meta-analysis - Shuai, Hui; Duan, Xi; Wu, Tao (Frontiers in Oncology, 2023)
Literature regarding experience with 3D laparoscopy about prostatectomy has remained scanty, and this could be related to the rise of robotic assisted laparoscopic surgery. This study aimed to perform a systemic review and meta-analysis to evaluate the perioperative, functional, and oncologic outcomes between 3D and 2D laparoscopic radical prostatectomy (LRP). We systematically searched the PubMed, Embase, and Cochrane Library databases for studies that compared perioperative, functional, or oncologic outcomes of both 3D and 2D LRP. The Newcastle-Ottawa Scale (NOS) tool and Jadad scale were used to assess the risk of bias in the included studies. Review Manager 5.3 was used for the meta-analysis. Seven studies with a total of 542 patients were included in the analysis. Among them, two were RCTs. There was no difference between groups in terms of preoperative characteristics.Anastomosis time, hospital day, and overall complication rates were similar in 3D than 2D group. However, operative time [mean difference (MD) -36.96; 95% confidence interval [CI] -59.25 to -14.67; p = 0.001], blood loss (MD -83.5; 95% CI -123.05 to -43.94; p <0.0001), and days of drainage (MD -1.48; 95% CI -2.29 to -0.67; p = 0.0003) were lower in 3D LRP. 2D and 3D LRP showed similarity in the positive surgical margin (PSM) rate and biochemical recurrence (BCR) rate at 3, 6, and 12months postoperatively. Additionally, there was no significant differences in continence and potency recovery rate between two group except higher continence rate of 3D LRP at 3 months. Current evidence shows that 3D LRP offers favorable outcomes compared with 2D LRP, including operative time, blood loss, days of drainage, and early continence. However, there was no conclusive evidence that 3D LRP was advantaged in terms of oncologic and functional outcomes (except for continence rate at 3 months).